2021
DOI: 10.2147/cmar.s311094
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Inflammatory Markers in Nasopharyngeal Carcinoma Patients in the Intensity-Modulated Radiotherapy Era

Abstract: Purpose: Inflammatory markers have been widely used in various cancers, but rarely in nasopharyngeal carcinoma (NPC). Here, we evaluated the prognostic value of pretreatment neutrophil-to-lymphocyte ratio (NLR), platelet-lymphocyte-ratio (PLR), systemic immune index (SII), and systemic inflammation response index (SIRI) on NPC in the intensitymodulated radiotherapy (IMRT) era. Methods: We retrospectively analyzed data from NPC patients from the Renmin Hospital of Wuhan University, between January 2012 and July… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“… 8 , 13 The systemic immune-inflammation index (SII), another integrated index based on platelet count and NLR, has been shown to be associated with OS and PFS in NPC patients with an approximate AUC value of 0.6 for OS. 10 , 11 , 15 , 32 An elevated neutrophil to lymphocyte ratio (NLR) is associated with a lower survival rate and worse treatment response to chemotherapy with an AUC value of 0.619 for OS. 11 , 12 , 14 , 33 , 34 Li et al proposed an index combining the C-reactive protein to albumin ratio and platelet to lymphocyte ratio, resulting in an AUC value of 0.670 for OS prediction.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“… 8 , 13 The systemic immune-inflammation index (SII), another integrated index based on platelet count and NLR, has been shown to be associated with OS and PFS in NPC patients with an approximate AUC value of 0.6 for OS. 10 , 11 , 15 , 32 An elevated neutrophil to lymphocyte ratio (NLR) is associated with a lower survival rate and worse treatment response to chemotherapy with an AUC value of 0.619 for OS. 11 , 12 , 14 , 33 , 34 Li et al proposed an index combining the C-reactive protein to albumin ratio and platelet to lymphocyte ratio, resulting in an AUC value of 0.670 for OS prediction.…”
Section: Discussionmentioning
confidence: 99%
“… 10 , 11 , 15 , 32 An elevated neutrophil to lymphocyte ratio (NLR) is associated with a lower survival rate and worse treatment response to chemotherapy with an AUC value of 0.619 for OS. 11 , 12 , 14 , 33 , 34 Li et al proposed an index combining the C-reactive protein to albumin ratio and platelet to lymphocyte ratio, resulting in an AUC value of 0.670 for OS prediction. 35 One advantage of these studies is that indicators of routine clinical detection can be used.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies have demonstrated that SII is related to the prognosis of solid tumors, such as hepatocellular carcinoma [ 11 ], esophageal squamous cell carcinoma [ 13 ], gastric cancer (GC) [ 14 ], pancreatic cancer [ 15 , 16 ], breast cancer [ 17 ], lung cancer [ 18 , 19 ], oral cancer [ 20 ], and other cancers. Several recent studies also showed the SII to b prognostic for NPC [ 21 26 ], although the results were inconsistent. For instance, in some studies [ 21 23 ], SII was reported as an independent prognostic factor for NPC; however, in other studies [ 24 26 ], SII was not documented as an independent prognostic factor for NPC.…”
Section: Introductionmentioning
confidence: 99%